Bilateral Olecranon and Left Lesser Trochanter Avulsion Fractures in Renal Osteodystrophy: A Rare Case Report and Comprehensive Review - Papineni, Vijay; Botchu, Rajesh; Iyengar, Kartikeyan P.; Chapala, Shashank; Shah, Asad Rabbani; Rathinavelu, Balamurugan (Acta medica Lituanica, 2025)
Chronic Kidney Disease-Mineral and Bone Disorder (CKD-MBD) disrupts phosphorus and calcium metabolism, leading to skeletal disorders such as demineralization, weakened bones, and an increased fracture risk. These disorders, known as renal osteodystrophy, vary widely and are classified into secondary hyperparathyroidism, adynamic bone, and osteomalacia based on bone turnover. Fracture risk increases with the severity of CKD, particularly in advanced stages (creatinine clearance
Keywords: avulsion fractures; femur; olecranon process; Chronic Kidney Disease-Mineral and Bone Disorder; radiography; ultrasonography; Magnetic Resonance Imaging